Hot Spots Policing: What We Know and What We Need to Know. (May 2014) - Weisburd, David; Telep, Cody W.
After reviewing the evidence regarding the general effectiveness of hot spots policing (what we know), we focus on areas where new knowledge must be developed (what we need to know). These include the importance of considering the impact of hot spots approaches on non-spatial displacement; assessing what strategies are most effective in addressing hot spots; examining how hot spots policing affects police legitimacy; evaluating whether hot spots policing will be effective in smaller cities and rural areas; investigating the long-term impacts of hot spots policing; and considering whether the adoption of hot spots policing will reduce overall crime in a jurisdiction.